Rola patentów na rynku oprogramowania - Galewski, Tomasz (The Role of Patents in the Software Market, 2008)
This article describes the problem of software patenting in the European Union. Patents can play an important role in the software market because they can reduce competition and eliminate smaller market-players. As a reference, the functioning of American software patents was shown. The EU institutions have to take into account presented problems while creating a new patent directive.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 68-78